Analisis Penerapan Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah (SAK EMKM) dalam Penyusunan dan Penyajian Laporan Keuangan pada Entitas Berbentuk Persekutuan: Studi Kasus pada CV XYZ - Gebby Amara Putri Sugeng Hariyanto; Ajeng Ayun Dining Utami; Yashinta Khairani; Siti Rodiah (Politeknik Negeri Padang, 2025)
This study aims to analyze the extent of the application of the Financial Accounting Standards Statement (SAK-EMKM) in the preparation and presentation of financial statements in partnership entities, with a case study of CV XYZ. The research method used is a qualitative approach, which allows for an in-depth understanding of the accounting practices applied by the company. This study uses a case study method with a focus on one entity, namely CV XYZ, to obtain a concrete picture related to the application of accounting standards. Data analysis techniques used include data reduction, narrative data presentation, and inductive conclusion drawing based on the results of in-depth interviews with finance employees. The results of the study indicate that CV XYZ has applied the basic principles of SAK-EMKM, such as separation of financial accounts, use of journal-based accounting software, and accrual revenue recognition. However, the application is not yet fully optimal because the financial statements are not yet equipped with notes to the financial statements, statements of changes in equity, and cash flows that comply with standards, and have not been externally audited. Therefore, although there are efforts towards SAK-EMKM compliance, improvements in the aspects of formal reporting and accountability are still very much needed.